The PI3K/AKT Pathway Inhibitor ISC-4 Induces Apoptosis and Inhibits Growth of Leukemia in Preclinical Models of Acute Myeloid Leukemia - Annageldiyev, Charyguly; Tan, Su-Fern; Thakur, Shreya; Dhanyamraju, Pavan Kumar; Ramisetti, Srinivasa R.; Bhadauria, Preeti; Schick, Jacob; Zeng, Zheng; Sharma, Varun; Dunton, Wendy; Dovat, Sinisa; Desai, Dhimant; et al. (Frontiers in Oncology, 2020)
Acute myeloid leukemia is a heterogeneous disease with a 5-year survival rate of 28.3%, and current treatment options constrained by dose-limiting toxicities. One of the key signaling pathways known to be frequently activated and dysregulated in AML is PI3K/AKT signaling. Its dysregulation is associated with aggressive cell growth and drug resistance. We investigated the activity of Phenybutyl isoselenocyanate (ISC-4) in primary cells obtained from newly diagnosed AML patients, diverse AML cell lines, and normal cord blood cells. ISC-4 significantly inhibited survival, and clonogenicity of primary human AML cells without affecting normal cells. We demonstrated that ISC-4-mediated p-AKT inhibition caused apoptosis in primary AML (CD34+) stem cells and enhanced efficacy of cytarabine. ISC-4 slowed leukemia progression with improved overall survival in a syngeneic C1498 mouse model with no discernable toxic effects on normal myelopoiesis. Reduced bone marrow leukemic burden was observed in a U937 human AML xenografted NRG mice treated with ISC-4 or cytarabine alone and the effect was enhanced with combination treatment. Together, the present findings suggest that ISC-4 might be a promising agent for AML treatment.